Elucidating the causal association between gut microbiota and intrahepatic cholangiocarcinoma through Mendelian randomization analysis - Chen, Zhitao; Shi, Weiguang; Chen, Kailei; Lu, Chicheng; Li, Xinyuan; Li, Qiyong (Frontiers in Microbiology, 2023)
Intrahepatic cholangiocarcinoma (ICC) is an aggressive liver cancer with poor prognosis. The gut microbiota has been linked to ICC, but evidence for causality is lacking. Elucidating causal gut microbiota-ICC links could inform prevention and treatment strategies.We performed a two-sample Mendelian randomization (MR) study to investigate causal associations between gut microbiota and ICC risk. Genome-wide significant single nucleotide polymorphisms (SNPs) associated with gut microbiota abundances were utilized as instrumental variables (IVs).Multiple methods assessed causality and sensitivity analyses evaluated result robustness.Bioinformatics analysis of genetic loci linked to gut microbiota and ICC examined potential mechanisms.Genetically predicted increases in Veillonellaceae, Alistipes, Enterobacteriales and Firmicutes were suggestively associated with higher ICC risk, while increases in Anaerostipes, Paraprevotella, Parasutterella and Verrucomicrobia appeared protective. Bioinformatics analysis revealed differentially expressed genes near gut microbiota-associated loci may influence ICC through regulating pathways and tumor immune microenvironment.Our findings provide suggestive evidence for causal links between specific gut microbiota and ICC risk.